Handbook of applied econometrics. (Blackwell, 1999)
Index number and factor demand approaches to the estimation of productivity. Frontier production functions. Consumer demand systems and household equivalence scales. Empirical analyses of inequality and welfare. Estimating models of dynamic optimization with microeconomic data...